Reaping IT Externality Benefits Across Business Units in Multibusiness Firms - Havakhor, Taha; Rahman, Mohammad Saifur; Setia, Pankaj (Production and Operations Management, 2026)
The indirect productivity gains related to information technology (IT), known as IT externalities, in inter-firm contexts have been extensively studied. However, the impact of IT investments within a business unit (BU) of a multibusiness firm on the productivity of other BUs remains unclear. Additionally, the conditions that facilitate such intra-firm externalities are not well understood. Research on resource externalities within multibusiness firms typically focuses on capacity-sharing benefits, where unused capacity in one unit can be utilized by another. IT resources, however, often lack capacity-sharing potential due to their full utilization or contractual limitations. Despite this, IT resources can generate non-rivalrous intangibles, such as internally developed applications, expertise, and consulting know-how, which can be shared within the firm to create externalities. This study investigates whether IT centralization (ITC), as a vertical coordination mechanism, is effective in harnessing IT externality potential arising from IT portfolio similarities (ITPSs), a form of horizontal coordination, across BUs. Utilizing data from 8,374 unique units within 866 firms from 2005 to 2020, we find that BUs must meet two conditions—higher ITPS and higher levels of ITC—to realize greater intra-firm IT externality benefits. Furthermore, these benefits accrue from IT investments made by units with a sufficient number of IT employees. Interestingly, BUs with limited access to IT employees gain more from pooled IT investments. Our findings suggest that concurrent vertical and horizontal coordination, along with access to human talent for creating knowledge, code, and expertise from digital resources, are crucial for maximizing digital resource externalities.